2021
DOI: 10.3892/etm.2021.9860
|View full text |Cite
|
Sign up to set email alerts
|

Role of targeted and universal mupirocin‑based decolonization for preventing surgical‑site infections in patients undergoing cardiothoracic surgery: A systematic review and meta‑analysis

Abstract: The purpose of the present study was to provide a systematic literature review and pool evidence on the efficacy of mupirocin-based decolonization protocol in reducing surgical-site infections (SSIs) in patients undergoing cardiothoracic (CT) surgery based on their Staphylococcus ( S .) aureus carrier state. The PubMed, Embase, Ovid, BioMed Central, Cochrane Central Register of Controlled Trials and Google Scholar databases were searched for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The 2013 American Society of Health-System Pharmacists Guideline for Antimicrobial Prophylaxis in Surgery recommends screening for S. aureus and to decolonize with mupirocin if patients test positive (Bratzler et al, 2013). Although there are conflicting data to support routine MRSA decolonization, the supporting evidence is the strongest in cardiothoracic and orthopaedic surgical patients (George et al, 2016; Schweizer et al, 2013; Wang et al, 2021). Studies are often limited by observational design, sample size, lack of standard decolonization procedures, or risk of bias.…”
Section: Decolonization With Mupirocinmentioning
confidence: 99%
“…The 2013 American Society of Health-System Pharmacists Guideline for Antimicrobial Prophylaxis in Surgery recommends screening for S. aureus and to decolonize with mupirocin if patients test positive (Bratzler et al, 2013). Although there are conflicting data to support routine MRSA decolonization, the supporting evidence is the strongest in cardiothoracic and orthopaedic surgical patients (George et al, 2016; Schweizer et al, 2013; Wang et al, 2021). Studies are often limited by observational design, sample size, lack of standard decolonization procedures, or risk of bias.…”
Section: Decolonization With Mupirocinmentioning
confidence: 99%
“…This most likely resulted from the heterogeneity of the groups in included studies. In turn, a recent systematic review and meta-analysis based on 17 studies, including a total of over 26,000 post-sternotomy patients, revealed a significant SSI reduction in a group undergoing decolonisation [ 98 ]. Despite partially contradictory results of studies regarding the effectiveness of S. aureus eradication in SSI prevention, most scientific societies clearly recommend this procedure [ 7 , 8 , 26 , 66 , 83 , 99 ].…”
Section: Ssi Preventionmentioning
confidence: 99%
“…Using chlorhexidine gluconate to cleanse the mouth, nose, and body can decrease total NI content by one fourth (10), and preoperative chlorhexidine mouthwash has been found to nearly halve the risk of postoperative pneumonia (12). Intranasal mupirocin treatment is effective in lessening SA carriage and the total incidence of SSI, but the evidence remains controversial for MRSA-related SSI (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%